THE CAMPAIGN TO RAISE THE TOBACCO TAX IN MASSACHUSETTS - HEISER PF; BEGAY ME (Tufts Archival Research Center, 2007)
Article on the campaign to raise the tobacco tax in Massachusetts. Concludes that the tax passed because of a favorable policy environment, the assembly by activists of a large coalition of supporters, and the activists' efforts to counter industry claims about the effect of such a tax on small businesses and lower income smokers.